A Child is not Property, but Responsibility: The Voice of Photography in the Defense of Childhoods (Revista Apotheke, 2025)
This study, centered on the photographic exhibition Child in the Media: "A Child is not Property, but Responsibility," investigates how the appropriation and multiplication of children's images in contemporary media culture contribute to the violation of their rights. The research explores how these representations can reinforce children's subalternity and how photographic art can serve as an interventive tool to question and criticize these symbolic constructions, prompting reflection on the place of childhood in our society. Methodologically, the work adopts a qualitative approach, based on intervention-research, developed in three subsequent phases: (1) brainstorming and pre-production, focused on defining visual attributes and conceptual solutions for the creation of the images; (2) photographic production, a stage dedicated to the elaboration of the photographs according to the developed plan; and (3) post-production, which includes image processing and the formulation of a dissemination strategy for the exhibition. The analysis reveals that photography, by challenging established representations, can act as a powerful tool in promoting citizenship and raising awareness about social and cultural issues related to childhood.
Keywords: adult-centrism; brazilian children; photography; childhoods; rights violation